The Effect of Audiovisual Fable Storytelling Media on the Listening Skills of Children Aged 5–6 Years at PAUD Tunas Bangsa, Padang City - Nabila Muthia Rezky Maghfirah; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2026)
This research aims to examine the impact of using audiovisual fable storytelling media on the listening skills of children aged 5–6 years at PAUD Tunas Bangsa, Padang. The study was prompted by identified challenges in children's listening abilities, such as low concentration levels and difficulties in understanding or responding to simple narratives. Employing a quantitative approach with a pre-experimental one-group pretest–posttest design, the study involved 15 children chosen through purposive sampling. The five-day intervention utilized diverse audiovisual fables to maintain engagement, with data analyzed through observation rubrics, normality tests, and paired sample t-tests. The results demonstrated a substantial improvement in average scores, rising from 28.96 during the pretest to 61.46 in the posttest. With a significance value of 0.000 (p < 0.05), the study concludes that audiovisual fable storytelling is a highly effective medium for significantly enhancing the listening competencies of young children.